Importance of Technology, Innovation and R&d In Increasing The Competitive Capacity of SMEs In Turkey - Erdil Şahin, Begüm; Dündar, Efe (International Finance Banking & Insurance Congress, 2012)
Small and Medium Enterprises (SMEs) have significant contributions to economic growth due to their flexible structures which help them develop technology and adapt to the rapidly changing market conditions in the condensing competition atmosphere as a result of globalization. Within this framework, SMEs have a significant role in increasing employment, investments, and export all around the world as well as in Turkey. It is necessary to develop new technologies and produce by using new methods in order to have and maintain a superior position in competition. SMEs started to become committed to research and development (R&D) activities especially in recent years. However, one of the most significant problems SMEs is the lack of financing in developing new technologies and R&D activities. A number of organizations in Turkey support SMEs in order to form highly innovative SMEs which are strong in international markets. Furthermore, with the incentives and policies executed, competitive capacities of SMEs are supported. The objectives of this study are to present the importance of technological innovations and R&D for SMEs in Turkey as essential factors of compatibility. Within this framework, this study deals with the notion and definition of SMEs in Turkey and in the European Union, place and importance of SMEs in the economy, and the problems that SMEs experience. Furthermore, after presenting the importance of technology, innovation, and R&D for compatibility of SMEs, the problems regarding R&D activities, the supports and policies for increasing the competition capacity in Turkey and finally the supports supplied in the European Union are evaluated.
Keywords: Small and Medium Enterprises (SME); Technology; Innovation; R&D; Competition; Turkey